The Relationship between Exercise Intensity and Stress Levels in Athletes - Adam Erlangga (Indonesian Journal of Global Health Research, 2025)
Stress is one of the factors that affect mental health and athletic performance. In student athletes, the demands of intensive training and academics can increase the risk of severe stress. This study aims to analyze the relationship between training intensity and stress levels in athletes at the North Sumatra Student Sports Education and Training Center. The study uses a quantitative approach with a descriptive analytical design and cross-sectional method. The study population consisted of 142 active athletes, with purposive sampling technique. The sample size was determined using the Slovin formula with a 5% error rate, resulting in 90 respondents. Data were collected using the Perceived Stress Scale (PSS-10) and International Physical Activity Questionnaire-Short Form (IPAQ-SF) questionnaires. The instruments were tested for validity through item-total correlation (all items were valid) and reliability using Cronbach's Alpha (>0.70), which showed good internal consistency. The results showed that most athletes were involved in high-intensity training and experienced high levels of stress, both in cardiorespiratory sports (56.8% high-intensity training; 73% high stress levels) and martial arts (67.9% high-intensity training; 75.5% high stress levels). Statistical analysis shows a significant relationship between training intensity and stress levels, with odds ratios (OR) of 6.42 for cardiorespiratory athletes and OR 8.58 for martial artists. These findings emphasize the importance of managing training intensity, monitoring stress levels, and implementing coping strategies to maintain athletes' mental health and performance.